2016
DOI: 10.18632/oncotarget.14077
|View full text |Cite
|
Sign up to set email alerts
|

SS31 Ameliorates age-related activation of NF-κB signaling in senile mice model, SAMP8

Abstract: Aging has been attributed to oxidative stress and inflammatory response, in which NF-κB and Nrf2-ARE signaling pathways play significant roles. Senescence accelerated mouse prone 8 (SAMP8) is generally used an animal model for aging studies. Here, we investigated the NF-κB and Nrf2-ARE signaling pathways in SAMP8 brains at different ages and their responses to SS31 peptide treatment. Thirty six SAMP8 mice were separated into aging groups and SS31-treatment groups. The hippocampus from each mouse was dissected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 43 publications
(47 reference statements)
1
9
0
Order By: Relevance
“…It is well known that aging is associated with inflammation, NF-κB activation, increased apoptosis, impaired mitochondrial activity, and a decline in immune function, as well as increased free-radical production rate [ 6 ]. Our results showed a decrease in pIκB expression levels in SAMP8 mice with RESV treatment (Figure 3B and 3C ), which is consistent with observations from previous studies [ 1 , 6 , 37 ]. Therefore, it is plausible that RESV can mediate anti-inflammatory and/or anti-oxidation effects via inhibiting NF-κB pathway.…”
Section: Disscusionsupporting
confidence: 93%
See 1 more Smart Citation
“…It is well known that aging is associated with inflammation, NF-κB activation, increased apoptosis, impaired mitochondrial activity, and a decline in immune function, as well as increased free-radical production rate [ 6 ]. Our results showed a decrease in pIκB expression levels in SAMP8 mice with RESV treatment (Figure 3B and 3C ), which is consistent with observations from previous studies [ 1 , 6 , 37 ]. Therefore, it is plausible that RESV can mediate anti-inflammatory and/or anti-oxidation effects via inhibiting NF-κB pathway.…”
Section: Disscusionsupporting
confidence: 93%
“…Aging is associated with an increasing prevalence of neurodegenerative disorders and leads to irreversible alterations in humans and experimental animals [ 1 ]. The retina, a layer of nervous tissue that covers the inside of the back of the eyeball, is exposed to a variety of environmental insults and stressors, including age-associated alterations and lighting that impair its function.…”
Section: Introductionmentioning
confidence: 99%
“…SS-31 is highly effective in increasing resistance to a broad range of diseases, including heart ischemia reperfusion injury ( Cho et al, 2007 ; Szeto, 2008 ), heart failure ( Dai et al, 2013 ), neurodegenerative disease ( Yang et al, 2009 ), and metabolic syndrome ( Anderson et al, 2009 ). In aged mice, SS-31 ameliorates kidney glomerulopathy ( Sweetwyne et al, 2017 ) and brain oxidative stress ( Hao et al, 2017 ) and has shown beneficial effects on skeletal muscle performance ( Siegel et al, 2013 ). We have recently shown that administration of SS-31 to 24-month-old mice for 8 weeks reverses the age-related decline in diastolic function, increasing the E/A from just above 1.0 to 1.22, restoring this parameter 35% toward that of young (5-month-old) mice ( Chiao et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…SS-31 is highly effective in increasing resistance to a broad range of diseases, including heart ischemia reperfusion injury (Cho et al, 2007;Szeto, 2008), heart failure (Dai et al, 2013), neurodegenerative disease (Yang et al, 2009) and metabolic syndrome (Anderson et al, 2009). In aged mice, SS-31 ameliorates kidney glomerulopathy (Sweetwyne et al, 2017) and brain oxidative stress (Hao et al, 2017) and has shown beneficial effects on skeletal muscle performance (Siegel et al, 2013). We have recently shown that administration of SS-31 to 24 month old mice for 8 weeks reverses the age-related decline in diastolic function, increasing the E/A from just above 1.0 to 1.22, restoring this parameter 35% towards that of young (5 month old) mice (Chiao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%